Analysis Of Micro Generator Performance From Porous Media Combustion - Basirah, Aiman (Universiti Sains Malaysia, 2022)
Porous media combustion is a combustion technology based on heating the ceramic material by using various gas to supply heat. The main purpose of the experiment was to gain data on the temperature from the porous media and value of voltage, current and power that produced by thermoelectric power generator peltier. As for proper project that based on fabricate model, CAD drawing that based on the actual products of fabricated model has been done. The CAD model has seven parts which are porous media, heatsink, ceramic material, thermoelectric power generator peltier, porcelain foam, burner, and butane gas. There is also exploded view in the CAD drawing to show actual positions of the parts. For the actual fabricated model, few parts fabricate by using few tools. Mini hand saw used to cut the cylinder and square shape of aluminum metal. However, cylindrical mild steel metal cut using saw machine. Mild steel metal welded to the burner and two part of aluminum metal of porous media welded by using MIG machine. Ceramic material put inside the square shape aluminum metal with the used of wire net in order to prevent the ceramic to move. Then, four thermoelectric power generator peltier stick to every side of porous media by using thermal plaster glue and same goes to four heatsink that stick after the thermoelectric power generator peltier in order to cool the thermoelectric power generator peltier from other side. The analysis done is to gain the moderate electrical power production from thermoelectric power generator peltier at stable temperature since porous media can retain heat at longer period of time.